PERAN PERANGKAT DESA DAN KOMPETENSI APARAT PENGELOLA DANA DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA TAHUN 2021 ( Studi Pada 8 Desa di Kecamatan Amahai, Kabupaten Maluku Tengah) - Utami Setya Ningsih; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the influence of the role of village officials and the competence of village fund managers on the accountability of village fund managers. The population in this study is the Amahai sub-district in the Central Maluku district. This study uses primary data. The method of collecting data in this study was through questionnaires given directly to respondents. In this study, there were 32 respondents. Data analysis used multiple linear regression. The results showed that the variables of the Role of Village Apparatus and Competence of Village Fund Management Apparatus simultaneously affected the Accountability of Village Fund Management. The Role of Village Apparatus variables does not affect Village Fund Management Accountability. The Competence of Village Fund Management Apparatus variable positively and significantly affects Village Fund Management Accountability.Keywords: Role of Village Apparatus, Competence, Village Fund Manager